Effect of pulsed electric field-assisted thawing on the gelling properties of pekin duck meat myofibrillar protein. (August 2023) - Chang, Chao-Kai; Lung, Chun-Ta; Gavahian, Mohsen; Yudhistira, Bara; Chen, Min-Hung; Santoso, Shella Permatasari; Hsieh, Chang-Wei
Abstract: This study aimed to investigate the effects of pulsed electric field (PEF)-assisted thawing at 1, 2, and 3 kV/cm on myofibrillar protein (MP) of Pekin duck meat compared with a control (untreated) sample. The results showed that 2 kV/cm had the highest water-holding capacity (WHC) at 82.22 ± 2.22%, followed by 3 kV/cm and 1 kV/cm. The analysis of MP water migration revealed that the proportion of immobilized water (P22 ) in MP treated with 2 and 3 kV/cm was 92.43% ± 0.59%, which was similar to that of the fresh sample group (93.43 ± 0.28%). Additionally, the thermal stability of myosin and actin in MP indicated that PEF-assisted thawing can reduce structural damage. These results showed that PEF can reduce structural damage to MP during thawing and minimize the loss of processing suitability in the meat processing industry. Highlights: 2 kV/cm PEF-assisted thawing reduces the loss of MP gel ability by about 40%. 2 kV/cm PEF can maintain MP WHC to 82.22 ± 2.22%, similar to fresh (85.37 ± 2.22%). The P22 of PEF treated MP (92.43 ± 0.59%) is similar to fresh (93.43 ± 0.28%). Surface hydrophobicity (28.81 ± 0.79) of PEF treated MP is similar fresh (26.89 ± 0.86). The denaturation of MP after thawing is improved by 2 kV/cm PEF.